The Influence of Financial Inclusion and the Ability to Pre-pare Financial Reports on the Financial Performance of Micro Businesses in the Culinary Sector in South Kota District - Nurfadila Nurfadila; Harun Blongkod; Amir lukum (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of financial inclusion and the ability to prepare financial reports on the financial performance of micro-enterprises in the culinary sector in South Kota District. This study uses a quantitative method. Data were collected through a questionnaire. Those selected as research samples based on purposive sampling techniques as a specific form of non-probability sampling were 125 respondents from micro-enterprises in South Kota. The data analysis technique in this study used Structural Equation Modeling (SEM) or a structural equation model operated through the Amos 24 program. The results of the study showed that financial inclusion has a positive influence on financial performance. On the other hand, the ability to prepare financial reports has no influence on financial performance. However, simultaneously these two independent variables contribute significantly to financial performance.